Step-to-step reproducibility and asymmetry to study gait auto-optimization in healthy and cerebral palsied subjects - Descatoire, A.; Femery, V.; Potdevin, F.; Moretto, P. (Annals of physical and rehabilitation medicine, 2009)
The purpose of our study was to compare plantar pressure asymmetry and step-to-step reproducibility in both able-bodied persons and two groups of hemiplegics. The relevance of the research was to determine the efficiency of asymmetry and reproducibility as indexes for diagnosis and rehabilitation processes. This study comprised 31 healthy young subjects and 20 young subjects suffering from cerebral palsy hemiplegia assigned to two groups of 10 subjects according to the severity of their musculoskeletal disorders. The peaks of plantar pressure and the time to peak pressure were recorded with an in-shoe measurement system. The intra-individual coefficient of variability was calculated to indicate the consistency of plantar pressure during walking and to define gait stability. The effect size was computed to quantify the asymmetry and measurements were conducted at eight footprint locations. Results indicated few differences in step-to-step reproducibility between the healthy group and the less spastic group while the most affected group showed a more asymmetrical and unstable gait. From the concept of self-optimisation and depending on the neuromotor disorders the organism could make priorities based on pain, mobility, stability or energy expenditure to develop the best gait auto-optimisation. Le but de notre étude était de comparer l’asymétrie des pressions plantaires et la reproductibilité pas-à-pas chez des personnes valides et dans deux groupes de sujets hémiplégiques en vue de déterminer la pertinence des indices d’asymétrie ou de reproductibilité dans les processus de diagnostic et de rééducation. Cette étude comprend 31 jeunes sujets sains et 20 jeunes sujets hémiplégiques divisés en deux groupes de dix sujets selon la sévérité de leurs troubles musculosquelettiques. Les pics de pression plantaire et le temps de survenue de ce pic étaient enregistrés avec un système de semelles embarquées. Le coefficient de variabilité intra-individuelle était calculé pour apprécier la stabilité du patron de marche. Un effect size était calculé pour quantifier l’asymétrie et les mesures étaient réalisées à huit endroits différents de l’empreinte plantaire. Les résultats montrent peu de différence de reproductibilité pas à pas entre les sujets sains et le groupe le moins spastique alors que le groupe le plus atteint montrait une marche asymétrique et instable. En ce qui concerne le concept d’auto-optimisation et en fonction des dysfonctionnements neuromoteurs, l’organisme pourrait choisir des priorités selon la douleur, la mobilité, la stabilité ou la dépense énergétique pour optimiser au mieux la marche.